Pengembangan E-Modul Tema 6 Cita-citaku Subtema 1 Aku dan Cita-citaku Pembelajaran 2 Berbasis Canva - Adelia Cahyati; Lina Novita; Rukmini Handayani (DIKDAS MATAPPA: Jurnal Ilmu Pendidikan Dasar, 2023)
Learning in class IV A still uses teaching materials in the form of printed books and is assisted by learning videos. This is considered boring and less interesting by students. The purpose of this research is to develop and produce digital teaching materials for Theme 6 Aspirations Sub-theme 1 Me and My Learning Goals 2 assisted by the Canva application which is suitable for use by fourth grade students at SDN Gunung Batu 01 by using research and development methods (Research and Development). and Development). The results of the study showed that there was an interest in student learning by using e-module teaching materials. Theme 6 Aspirations Sub-theme 1 I And My Aspirations for Learning 2 was assisted by the Canva application. The digital teaching materials developed were declared suitable for use based on the results of validation by media experts, linguists and material experts as well as student responses as users. Thus, it can be concluded that the teaching materials for the e-module Theme 6 Aspirations Sub-theme 1 I and Learning Aspirations 2 can be developed and are suitable for use by fourth grade students in elementary school.